Efficacy and Tolerability of a New Formulation in Rectal Ointment Based on Zn-L-Carnosine (Proctilor®) in the Treatment of Haemorrhoidal Disease - Pietroletti, Renato; Giuliani, Antonio; Buonanno, Alberto; Mattei, Antonella; Fiasca, Fabiana; Gallo, Gaetano (Frontiers in Surgery, 2022)
Haemorrhoidal Disease (HD) shows high prevalence in western countries reaching 4.4% per year in the US. Topical preparations are first line treatments, readily available as “Over the Counter” (OTC) products, often containing non standardized mixture of “natural” remedies, or anaesthetics or cortisol, those latter not free from undesirable effects. Zinc-L-Carnosine is a cytoprotective compound, promoting mucosal repair in the gastrointestinal tract and also in mucosal repair following radiation injuries to the rectum as well as in ulcerative colitis. Our aim was to study the efficacy of Zinc-L-Carnosine in relieving acute symptoms of HD, testing a preparation in rectal ointment, Proctilor®, in patients complaining of bleeding or thrombosed piles. In a multicentre open trial, 21 patients older than 18 yrs of age were enrolled. Symptoms of HD were graded according to the Haemorrhoidal Disease Symptoms Score (HDSS) in association with the Short Health Scale (SHS) to assess the influence of HD on quality of life. Pain was assessed with VAS score, bowel habit by means of Bristol scale. Patients were evaluated at enrolment (T0) and at two (T1) and four (T2) weeks of treatment with Proctilor® rectal ointment. There were 10 males, and 11 females mean age 49yr. Pain, bleeding or thrombosis were all significantly reduced after treatment; mean VAS score decreased from 4.71±3.05 at T0 to 0.52±0.87 and 0.05±0.22 at T1 and T2 respectively; (mean±SD; p<0.001 in both cases). Similarly, the HDSS score showed to be significantly reduced between T0, T1 (8.05±4.55 vs 1.14±1.01), and T2 (8.05±4.55 vs 0.24±0.44) (mean±SD; p<0.001 in both cases). Quality of life showed to be improved as SHS score decreased significantly with treatment (7.90±4.17 at T0 vs 4.24±0.44 at T1 vs 4.05±0.22 at T2; mean±SD; p<0.001 in both cases). Bristol score of defecation remained substantially unchanged. No side effects neither discontinuation of treatment was reported. Results of our investigation, suggest a role of Proctilor® rectal ointment in treating symptomatic HD with good results and excellent safety profile. However, our preliminary results encourage further studies on a larger number of patients to confirm the role of Zinc-L-Carnosine in rectal ointment for the topical treatment of HD.